ANALISIS KONSEPTUAL SEJARAH NASIONAL INDONESIA SEBAGAI BASIS EPISTEMOLOGIS PEMBELAJARAN PPKN DALAM MEMBANGUN WARGA NEGARA DEMOKRATIS - Yonathan Anjulin Kamlasi; Fadil Mas’ud; Maria Cindiany Baru; Esty Jumirna Taneo; Emilia Nadya Pa’a; Maria Fransiska Mika; Maria Sipriani Dau; Erikson Agung Bau; Oktaviana Mopia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the conceptual role of Indonesian national history as an epistemological foundation in Civic Education (PPKn) for fostering democratic citizens. The research is motivated by the declining quality of democratic practices, reflected in low political participation, rising intolerance, and weak internalization of democratic values among students. The study aims to analyze how national history can function as a critical and reflective knowledge base to strengthen civic competence. This research employs a qualitative approach using library research combined with conceptual analysis. Data were collected from primary and secondary sources, including academic books, peer-reviewed journal articles, and relevant educational documents published within the last decade. The analysis was conducted through content analysis and a hermeneutic-critical approach to interpret and synthesize key concepts related to history and civic education. The findings reveal that national history contains essential democratic values such as justice, equality, tolerance, and participation, which can serve as a strong epistemic foundation for PPKn learning. However, current instructional practices remain largely normative and cognitive-oriented, limiting students’ ability to develop historical reflection and critical thinking. The integration of historical perspectives into civic education is shown to enhance students’ analytical skills, democratic awareness, and active participation. Therefore, reconstructing PPKn learning through a historically grounded, reflective, and dialogical approach is crucial for developing democratic, critical, and responsible citizens in contemporary society.